Use of Exhaled Nitric Oxide as a Biomarker in Diagnosis and Management of Chronic Obstructive Pulmonary Disease. (April 2016) - Arif, Ahmed A.; Mitchell, Colin
Background: Chronic obstructive pulmonary disease (COPD), a progressive and nonreversible disease, is a leading cause of mortality and morbidity throughout the world. Because airway inflammation is a hallmark of COPD, it has been proposed that measuring exhaled nitric oxide, a marker of inflammation, in exhaled breath condensate could prove to be an inexpensive and efficient method to detect COPD in outpatient settings.Methods: This study used secondary data on a sample of 10, 214 individuals 30 years and older from the National Health and Nutrition Examination Survey 2007 to 2010. Binary and ordinal logistic regression analyses were used to test the association of exhaled nitric oxide (eNO) with COPD and COPD severity.Results: The prevalence of COPD was 7.2%, based on self-reported physician diagnoses and 11.4% based on prebronchodilator spirometry analysis. This study found no statistically significant association between eNO, COPD, and COPD severity ( P > .05).Conclusions: The findings of this study do not support use of eNO as a biomarker of inflammation in diagnosis and management of COPD.